PEMANFAATAN SERBUK GERGAJI KAYU UNTUK PEMBUATAN BONEKA HORTA DAN BRIKET DI DESA MUNCAN - Zulriani, Evi; Kurniawati, Ade; Astira, Ayuni; Maab, Husnul; Maulana, Lalu Dicky Achmad; Imam, Muhammad; Jaelani, Muhammad Putra; Hidayah, Rahmiza; Hasanah, Uswatun (Universitas Mataram, 2024)
Muncan Village, Central Lombok Regency is one of the villages where the majority of its hamlets are furniture industry centers. Based on demographic data from the population, Muncan Village is a village where the majority of residents work as furniture entrepreneurs. The results of this furniture business produce by-products, namely wood sawmill waste. This sawmill waste has not been utilized by residents. This community service aims to provide information to the residents of Muncan Village about whether sawmill waste can be used to make horta (horticultural) dolls as decoration or tourism educational packages and briquettes as a tool for baking which later, if developed, will increase the income of the residents of Muncan Village. Kopang District, Central Lombok Regency. This community service was carried out on Saturday, February 3 2024 with the theme